Essays in Capital Mobility, Growth, and Macroeconomic Volatility - (:unkn) unknown (My University, 2013)
This dissertation comprises three chapters in international macroeconomics. Specifically, we focus on international financial integration and its linkage to economic growth and volatility. In Chapter 1, we revisit the Feldstein-Horioka (1980) puzzle that saving-investment correlation exhibits a pattern contrary to expectation, being higher among the OECD countries that are more financially integrated and lower among emerging markets economies with less financial integration and greater capital controls. We find that the evolution of FH coefficient is highly consistent with increased financial integration over time, thus resolving the puzzle dynamically. We also explain the cross-country component of the puzzle by showing that financial market imperfections influence how well FH coefficient measures capital mobility. In chapter 2, we study the linkage between financial integration and economic growth. We develop a dynamic stochastic model that generalizes Obstfeld's (1994) model by incorporating the costs from systemic risk besides the well-known benefit from risk-sharing by Obstfeld (1994). We show that potential cost from the systemic risk could lower the benefit from risk diversification in an integrated financial market. By using the stock market data from Taiwan and US to calibrate the model, we find that the predictions of the model are consistent with actual data on growth. In chapter 3, we study the relationship between financial integration and economic volatility. Prior research that has studied this relationship has not explored the potentially distinct effects of capital inflows and capital out flows on volatility. Our contribution is to make this crucial distinction conducting our analysis. We find that non-OECD countries with higher levels of external debt assets are associated with lower consumption volatility, and external debt liabilities are associated with higher consumption volatility. This finding is insignificant for OECD countries.
Keywords: Capital Mobility; Economic Growth; Financial Integration; Macroeconomic Volatility; Systemic Risk